Modulation of IL-6 Expression by KLF4-Mediated Transactivation and PCAF-Mediated Acetylation in Sublytic C5b-9-Induced Rat Glomerular Mesangial Cells - Xia, Lu; Liu, Yu; Zhang, Zhiwei; Gong, Yajuan; Yu, Tianyi; Zhao, Dan; Qiu, Wen; Wang, Yingwei; Zhang, Jing (Frontiers in Immunology, 2022)
Interleukin-6 (IL-6) overproduction has been considered to contribute to inflammatory damage of glomerular mesangial cells (GMCs) in human mesangial proliferative glomerulonephritis (MsPGN) and its rat model called Thy-1 nephritis (Thy-1N). However, the regulatory mechanisms of IL-6 expression in GMCs upon sublytic C5b-9 timulation remain poorly understood. We found that Krüppel-like factor 4 (KLF4) bound to the IL-6 promoter (−618 to −126 nt) and activated IL-6 gene transcription. Furthermore, lysine residue 224 of KLF4 was acetylated by p300/CBP-associated factor (PCAF), which was important for KLF4-mediated transactivation. Moreover, lysine residue 5 on histone H2B and lysine residue 9 on histone H3 at the IL-6 promoter were also acetylated by PCAF, which resulted in an increase in IL-6 transcription. Besides, NF-κB activation promoted IL-6 expression by elevating the expression of PCAF. Overall, these findings suggest that sublytic C5b-9-induced the expression of IL-6 involves KLF4-mediated transactivation, PCAF-mediated acetylation of KLF4 and histones, and NF-κB activation in GMCs.